Retribution for Social Capital Based Household Waste Handling Services - Triono, Agus; Putri, Ria Wierma; Febiola, Cahya Putri (Jurnal Pembaharuan Hukum, 2025)
The issue of hygiene and household waste management in Indonesia is becoming increasingly urgent. A public culture that does not care about cleanliness and the environment is the main challenge. Ironically, while 65 million tons of waste are generated each day, a mere 7% of it is recycled. This research utilizes normative methods, focusing on both statutory and conceptual approaches, to explore relevant legislation and legal concepts related to waste management. This research highlights the lack of research that emphasizes the social capital aspect of waste management and proposes a social capital-based waste service levy model as a solution. The research results show that low public awareness, lack of infrastructure, and weak implementation of regulations are the main problems in waste management in Indonesia. The social capital-based retribution model, which involves the use of special plastic bags and active community participation, is expected to increase the effectiveness and efficiency of waste management. This approach utilizes existing social networks and norms, encourages communities to be more responsible in managing their household waste, and creates a fairer and more transparent retribution mechanism. Thus, this research provides a new contribution in efforts to create a cleaner and healthier environment in Indonesia.